Controlling solid–liquid–solid GeSn nanowire growth modes by changing deposition sequences of a-Ge:H layer and SnO2 nanoparticles. (3rd June 2021) - Gong, Ruiling; Azrak, Edy; Castro, Celia; Duguay, Sébastien; Pareige, Philippe; Roca i Cabarrocas, Pere; Chen, Wanghua
Abstract: Alloying Ge with Sn is one of the promising ways for achieving Si compatible optoelectronics. Here, GeSn nanowires (NWs) are realized via nano-crystallization of a hydrogenated amorphous Ge (a-Ge:H) layer with the help of metal Sn droplets. The full process consists of three steps: (1) SnO2 nanoparticle (NP) reduction in a hydrogen plasma to produce Sn catalyst; (2) a-Ge:H deposition at 120 °C and (3) annealing. GeSn alloys with rich morphologies such as discrete nanocrystals (NCs), random, and straight NWs were successfully synthesized by changing process conditions. We show that annealing under Ar plasma favors the elaboration of straight GeSn NWs in contrast to the conventional random GeSn NWs obtained when annealing is performed under a H2 atmosphere. Interestingly, GeSn in the form of discrete NCs can be fabricated during the deposition of a-Ge:H at 180 °C. Even more, the synthesis of out-of-plane GeSn NWs has been demonstrated by reversing the deposition sequence of SnO2 NPs and a-Ge:H layer.